Evaluation and Correction of the Radiometric Calibration Biases in MERSI-RM/FY-3G Middle Infrared and Thermal Infrared Channels Against MODIS/Aqua Channels - Jiang, Ming-Xu; Jiang, Geng-Ming; Chen, Hao (IEEE transactions on geoscience and remote sensing, 2025)
The accurate and stable radiometric calibration is a fundamental for quantitative remote sensing. This article addresses the evaluation and correction of radiometric calibration biases in the middle infrared channel (channel 6 centered at 3.8~μ m) and the thermal infrared channels (channels 7 and 8 centered at 10.8 and 12.0~μ m, respectively) of the MEdium Resolution Spectral Imager for the Rainfall Mission (MERSI-RM) on FengYun-3G (FY-3G) satellite against the channels of the Moderate Resolution Imaging Spectroradiometer (MODIS) on Aqua satellite using the double-difference (DD) method. First, an infrared radiative transfer model is constructed to simulate the observations in both middle infrared and thermal infrared channels, in which surface reflected solar irradiances are fully taken into account. Then, the matching samples between the MERSI-RM and MODIS observations in January, April, July, and October of 2024 are collected in terms of the matching criteria. Next, the radiances at top of atmosphere (TOA) are simulated using the infrared radiative transfer model. Finally, the radiometric calibration biases in the MERSI-RM channels 6-8 are evaluated and corrected. The results show that the impact of the simulation errors, the spectral response differences, and geolocation errors on the final intercalibration results can be ignored. The radiometric calibration of the MERSI-RM channel 6 is quite consistent with that of the MODIS channel 20, while the radiometric calibrations in the MERSI-RM channels 7 and 8 are about 0.5-K underestimated. Although more or less calibration biases exist in the MERSI-RM channels, their on-orbit calibrations are generally stable in the four months of 2024.